Myth and argument - Campos Vargas, Henry (2018)
This paper offers an approach to the myth as argument. For example, in some contexts myth can be used as criteria of truth, authority argument, exemplum, cause of a phenomenon, term of an analogy, allegory and a mean in order to explain a thesis.